The evolution of containerization and its impact on the Maghreb ports - Arbia Hlali; Sami Hammami (Annals of Marine Science - Peertechz Publications, 2019)
This paper studied the evolution of container traffic in the global world and its impacts on the seaports Maghreb region (Tunisia, Algeria and Morocco). The containerization transformed the ports sector from one generation to another and developed the international trade between regions. The descriptive analysis realized in this study shows the interested impact of containerization in the global world specially the Asian ports which have attracted more benefits from the containerization. While, the status of Maghreb seaports is covered by several challenges. Thus, the weakness of the maritime infrastructure is the main lack for the three countries.